2019
DOI: 10.1038/s41598-019-55130-w
|View full text |Cite|
|
Sign up to set email alerts
|

Preconditioning the Initial State of Feeder-free Human Pluripotent Stem Cells Promotes Self-formation of Three-dimensional Retinal Tissue

Abstract: A three-dimensional retinal tissue (3D-retina) is a promising graft source for retinal transplantation therapy. We previously demonstrated that embryonic stem cells (ESCs) can generate 3D-retina in vitro using a self-organizing stem cell culture technique known as SFEBq. Here we show an optimized culture method for 3D-retina generation from feeder-free human pluripotent stem cells (hPSCs). Although feeder-free hPSC-maintenance culture was suitable for cell therapy, feeder-free hPSC-derived aggregates tended to… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
46
0

Year Published

2020
2020
2025
2025

Publication Types

Select...
8

Relationship

3
5

Authors

Journals

citations
Cited by 25 publications
(53 citation statements)
references
References 76 publications
5
46
0
Order By: Relevance
“…Retinal differentiation was conducted following the modified SFEBq method we recently reported ( Kuwahara et al., 2019 ; Yamasaki et al., 2021 ) (Nukaya et al. ; WO19/017,492, 054,514, 054,515).…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Retinal differentiation was conducted following the modified SFEBq method we recently reported ( Kuwahara et al., 2019 ; Yamasaki et al., 2021 ) (Nukaya et al. ; WO19/017,492, 054,514, 054,515).…”
Section: Methodsmentioning
confidence: 99%
“…Photoreceptor cell replacement therapy for retinal degenerative diseases including retinitis pigmentosa (RP) and age-related macular degeneration (AMD) is considered an attractive approach to restore visual function. The advance of innovative technology to generate self-organizing retinal organoids from mouse and human embryonic stem cells (ESCs) or induced pluripotent stem cells (iPSCs) enabled retinal tissue transplantation for end-stage retinal degeneration, with a stable supply of retinal cells that are qualitatively comparable with fetal retinal tissue or cells ( Eiraku et al., 2011 ; Kuwahara et al., 2015 , 2019 ; Meyer et al., 2009 ; Nakano et al., 2012 ; Reichman et al., 2014 ; Zhong et al., 2014 ). Transplantation of hESC/iPSC-retinal tissue-sheet (retinal sheet, here after) or cells has been conducted in animal models of end-stage retinal degeneration to show functional potential to elicit light responses in host retinal ganglion cells (RGC) and light-guided behaviors ( Iraha et al., 2018 ; Mandai et al., 2017 ; McLelland et al., 2018 ; Ribeiro et al., 2021 ; Tu et al., 2019 ; Zerti et al., 2021 ).…”
Section: Introductionmentioning
confidence: 99%
“…hiPSC-RPE cells were differentiated using the SFEBq method 21 23 . (See Supplementary methods for details).…”
Section: Methodsmentioning
confidence: 99%
“…About 80% of cells expressed eye field transcription factors, and 20% of cells expressed CRX markers after three weeks of culture in six‐well plates coated with Matrigel. Moreover, in 2011, Eiraku et al (2011) reported a breakthrough strategy to produce three‐dimensional structural retinal organoids (3D retina) from mouse ESCs using the SFEB method with quick aggregation (SFEBq).This protocol was adapted for hESCs (Nakano et al., 2012), and efficient methods such as the timed treatment of bone morphogenic protein 4 (BMP4) have been published (Kuwahara et al., 2015, 2019; Atsus). Other methods for 3D organoid formation have also been reported, including a protocol in which 3D organoids were mechanically picked up from two‐dimensional (2D) cultures during differentiation (Meyer et al., 2011; Reichman et al., 2014; Zhong et al., 2014), which was further optimized using a xeno/feeder‐free two‐step culture system for hiPSCs (Reichman et al., 2017).…”
Section: Regenerative Therapy Using Photoreceptor Cell Transplantatiomentioning
confidence: 99%